2003
DOI: 10.1021/np0204500
|View full text |Cite
|
Sign up to set email alerts
|

Briarellins J−P and Polyanthellin A:  New Eunicellin-Based Diterpenes from the Gorgonian Coral Briareum polyanthes and Their Antimalarial Activity

Abstract: A new chemical study of the hexane extract of the gorgonian Briareum polyanthes collected in Puerto Rico afforded 10 new diterpenes of the eunicellin class, briarellins 1-9 and polyanthellin A (10), along with the known diterpene briarellin D (11). The structures and relative stereochemistry of metabolites 1-10 were assigned on the basis of NMR studies, chemical methods, and comparisons to the spectral properties of 11. A reassessment of prior structural assignment for briarellin A and two known sclerophytin-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 24 publications
2
82
0
2
Order By: Relevance
“…One eunicellin-type diterpenoid astrogorgin G 169 has been repored from a Chinese gorgonian Astrogorgia sp., 89 92 and this study has also led to a revision of the structure of previously reported briarellin A 93 to 174. The structure originally assigned to 11-acetoxy-4-deacetoxyasbestinin F 94 has been revised to 175.…”
Section: Diterpenesmentioning
confidence: 59%
“…One eunicellin-type diterpenoid astrogorgin G 169 has been repored from a Chinese gorgonian Astrogorgia sp., 89 92 and this study has also led to a revision of the structure of previously reported briarellin A 93 to 174. The structure originally assigned to 11-acetoxy-4-deacetoxyasbestinin F 94 has been revised to 175.…”
Section: Diterpenesmentioning
confidence: 59%
“…Misassignments of single stereocenters (Table 7) near to correctly assigned centers are associated with interpretation of NOE data for structurally diverse compounds. For example, this is the case for brevenal, 61, 62 solandelactones A-H, 63, 64 ritterazines B 65, 66 and F, 67 netamines E and G, 68, 69 briarellin J, 70, 71 and dictyosphaeric acid A. 72, 73 Consideration of the source of these errors highlights the need for careful evaluation of all possible alternative molecular models that adhere to NOE constraints.…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…[2] (+)-1 has shown to exhibit cyctotoxity against A 549 (human lung adenocarcinoma) cell culture at an IC 50 of 18.33 mg mL À1 . [1] Two other soft-coral diterpenes sclerophytin A (2) [3,4] and polyanthellin A (3) [5,6] have shown high cytotoxicity and antimalarial activity, respectively. Their attractive molecular architectures and their diverse biological activities previously led to several ingenious total syntheses of some members of this natural product family by the research groups of Paquette, [3a,c] Overman, [3b,c, 7] Crimmins, [8] and Kim.…”
mentioning
confidence: 99%